Effects of left primary motor and dorsolateral prefrontal cortex transcranial direct current stimulation on laser-evoked potentials in migraine patients and normal subjects. (28th July 2016) - Vecchio, Eleonora; Ricci, Katia; Montemurno, Anna; Delussi, Marianna; Invitto, Sara; de Tommaso, Marina
Highlights: Dorsolateral prefrontal cortex (DLPFC) and motor cortex (M1) anodal tDCS modified habituation of the N2P2 complex of Laser Evoked Potentials. Habituation to painful stimuli increase after DLPFC stimulation in migraine, and it is reduced after M1 stimulation in both patients and healthy subjects. The prefrontal cortex tDCS induces a normalization of temporal processing trigeminal pain in migraine patients. The motor cortex tDCS exertes an up-grading of nociceptive cortex activation. Abstract: Migraine is characterized by an altered cortical excitability. Because transcranial direct current stimulation (tDCS) can change brain activity noninvasively, it is possible to hypothesize its efficacy in modulating pain in migraine. In this study, we compared the effects of tDCS of the left primary motor cortex (M1) and left dorsolateral prefrontal cortex (DLPFC) both on subjective pain and on evoked responses induced by laser stimulation (LEPs). Thirty-two patients and sixteen controls were randomized to receive sham stimulation and real tDCS with the anode centered over M1 or DLPFC. Laser Evoked potentials were recorded in basal, sham and tDCS conditions. We did not find significant acute changes in LEPs parameters and pain perception among subjects who received tDCS of both M1 and DLPFC. After DLPFC tDCS, we observed a significant increase of N2-P2 component habituation in migraine patients while M1 stimulation reduced it. These findings may suggest a modulation of abnormal pain processing induced by DLPFC and M1 anodal tDCS and outline the need for future investigations exploring the possible neuronal plasticity changes supporting the clinical effect on migraine.